Epidemiological and clinical outcome comparison of indirect (`strain`) versus direct (`contusion`) anterior and posterior thigh muscle injuries in male elite football players: UEFA Elite League study of 2287 thigh injuries (2001-2013) - Ueblacker, P.; Mueller-Wohlfahrt, H.-W.; Ekstrand, J. (British Journal of Sports Medicine, 2015)
Background Data regarding direct athletic muscle injuries (caused by a direct blunt or sharp external force) compared to indirect ones (without the influence of a direct external trauma) are missing in the current literature—this distinction has clinical implications.